INTERPRETING THE EXODUS AMONG THE NGONI PEOPLE - Zulu, Edwin (Scriptura, 2012)
The interpretation of the Ngoni of Exodus 14:21-31 makes a comparison with the Israelites possible. Both the Israelites and the Ngoni crossed an expanse of water to reach their new land; The Israelites crossed the Red Sea and the Ngoni crossed the Zambezi River. Moreover, just as God provided the Israelites passage by facilitating the crossing of the Red Sea on dry land in a miraculous way, the Ngoni were aided by the locals, the Chikunda people, by carrying them in their canoes to cross the river. The Egyptians perished in the sea; the Ngoni killed the Chikunda after being aided by them. The role of the King is also mentioned; in the biblical story Moses plays a significant role as the agent of God. In a similar manner, King Zwangendaba's role is highlighted in the entire episode. These narratives of origin and migration (both Biblical and Ngoni) are important for the formation of identity amongst the Ngoni in Zambia.   doi: 10.7833/108-1-9